Penerapan Media Pembelajaran Canva Ai Pada Mata Pelajaran Informatika Kelas X Di Sma Negeri 3 Gorontalo Utara - Puluhulawa, Alda Cahyani; Hadjaratie, Lillyan; Suhada, Sitti; Koniyo, Moh. Hidayat; Kadim, Ahmad Azhar; Bouty, Abd. Aziz (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
This research aims to develop learning media using Canva as a tool to help students improve their learning outcomes in the subject of Algorithms and Programming by creating Canva AI learning media that contains content capable of visualizing the material. The method used in this research is the Research and Development development method with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results of the feasibility test by content experts showed a feasibility score of 4.6 with the category "very valid" and by media experts with a feasibility score of 4.7 with the category "very valid." The practicality test based on teacher response data showed a percentage of 90.5% with the category "very practical" and student response data showed a percentage of 91.2% with the category "very practical." The effectiveness test showed a post-test learning outcome mastery of 82.1 with the category "very good." The effectiveness test based on the correlation sample test results from the post-test and pre-test showed 0.001 < 0.05, indicating a significant difference in student learning outcomes. Thus, it can be concluded that the application of the Canva AI learning media is feasible, practical, and effective for use in the learning process.Keywords: Learning Media, Canva AI, ADDIE, Informatics